Desinstitucionalização das medidas de segurança na Paraíba: entre controles e abandonos - Almeida, Olívia Maria de (2018)
After 17 years of approval of Law nº 10.216/2001, and even with Brazil's binding to the Convention on the Rights of Persons with Disabilities and the subsequent publication of the Brazilian Inclusion Law, the capacity of people in mental suffering for crimes continues to be disregarded, and the treatment of them, as a rule, is intended for hospitalization in judicial asylums. Another aggravating factor: there is no forecast of maximum temporal limitation and its release is conditional, giving room for the perpetuation of the enclosure, with the breaking of family ties and institutionalization, and for the attachment of the person who may be disinterned in this system. In view of the invisibility and the abandonment of this population, the elements of the Psychiatric Reform and the trajectory of the anti-asylum movement are persecuted in order to analyze the process of deinstitutionalization of the security measures, focusing on the cases of people who remain in the Penitenciária de Psiquiatria Forense do Estado da Paraíba (PPF/PB) with a desinterned verdict pronouncement. As methods of data collection, we initiate with documentary research, participant observation in PPF/PB, and then semi-structured interviews. For the interpretation of the material collected, qualitative analysis and content analysis are used, with the definition of the following analytical categories: institutionalization processes in the PPF/PB, Psychiatric Reform and deinstitutionalization of security measures. With the empirical research, it is verified that this system diffuses over the life of the people submitted to the security measure, which compromises the process of deinstitutionalization and produces a relation of institutional dependence. When investigating the professionals' perceptions, remains clear the distinct notions about the category of deinstitutionalization and the maintenance of a relationship of guardianship and prejudice with those subject to security measures. It is concluded that this system works against the Psychiatric Reform in its antimanicomial perspective, in view of being anchored in the notions of dangerousness and incomputability, which turns difficult to guarantee rights such as freedom, access to law and justice. Thus, it is urgent to consider the capacity of these people and transform the way the state, professionals and society relate to madness.